PR Stanley <[EMAIL PROTECTED]> writes:

> It's one of those things - I know sort of instinctively why it is so
> but can't think of the formal rationale for it:

> f g x = g (g x) :: (t -> t) -> (t -> t)

(t -> t) -> (t -> t)

So
   g :: t -> t 
   x :: t
Thus
   f :: (t -> t) -> t -> t

(The last parenthesis is not necessary, but implies that the type of
the partial application  f g  is a function t -> t .)

-k
-- 
If I haven't seen further, it is by standing in the footprints of giants
_______________________________________________
Haskell-Cafe mailing list
Haskell-Cafe@haskell.org
http://www.haskell.org/mailman/listinfo/haskell-cafe

Reply via email to